An examination of sociocultural factors influencing lifestyles, health and health-seeking behaviour : a case study of Malaysian Chinese cancer survivors - Yew, Wong Chin Vivien (Kulliyyah of Islamic Revealed Knowledge & Human Sciences,International Islamic University Malaysia, 2012)
This study of Malaysian Chinese cancer survivors aims at analysing the lifestyles, health and health-seeking behaviour of the cancer survivors. The focus of the study is primarily aimed at their early years of life and the ways they lived their lives. This includes their diets, leisure activities, work and social environments, perception of health, and health-seeking behaviours. While looking at these lifestyle components, the analysis of social and cultural factors in influencing their decision making on living and health-seeking behaviours was the focus of the study. 50 cancer survivors with different types of cancer were selected from the group of cancer survivors who frequent the Lembah Kiara Recreational Park in Kuala Lumpur; engaging in 'Guolin Qigong' exercise in the morning. Using qualitative methodology, this study employed participant observation technique as well as face-to-face informal interviews guided by a set of pre-set interview schedule. It is a general truth that the Malaysian Chinese have over the years inherited their forefathers' cultural beliefs and practices especially in their worldview of health and living. This is in turn related to the main finding of this study, which indicates that Chinese cultural beliefs and practices not only have a significant impact on the early lifestyle of the Malaysian Chinese cancer survivors, but also play a vital role in their interpretation and perception of health and illnesses as well as their needs for health care. In this study, the sociocultural values of the Malaysian Chinese community were consistently highlighted in the process of decision-making of the cancer survivors with regard to their lifestyle before cancer diagnosis and their health-seeking behaviours which include medical pluralism and cancer treatment options. Finally, this study holds an important implication in contributing to the literature of medical sociology, in particular, to the epidemiological study of cancer.